Analysis of the Availability and Utilization of Facilities and Infrastructure at SMPN 15 Mataram - Adelia Safitri; Jaufil Laili (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the availability and utilization of infrastructure at SMPN 15 Mataram as a crucial factor in supporting the teaching and learning process. This study examines the condition of available facilities, their utilization levels by teachers and students, and the effectiveness of their management in supporting academic and non-academic activities. This article explains how facilities such as classrooms, libraries, laboratories, and sports and technology facilities play a role in creating a conducive learning environment. The analysis shows that most facilities have been optimally utilized, although several limitations remain that require improvement to achieve better educational quality. These findings are expected to serve as a reference for the school in formulating strategies for sustainable infrastructure development. The importance of educational facilities and infrastructure within a school and supporting teaching and learning activities is also stated in Government Regulation Number 19 of 2005 in conjunction with Number 32 of 2013 concerning National Education Standards and Number 24 of 2007 concerning School Facilities and Infrastructure Standards.